2013
DOI: 10.3390/cancers5020511
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of Predictors for Rapid Progression in Prostate Cancer Patients Receiving Sipuleucel-T

Abstract: Sipuleucel-T is an immunotherapy indicated for the treatment of metastatic prostate cancer. It offers a new mechanism to treat prostate cancer without the side effects of hormone therapies and chemotherapies. In previous studies sipuleucel-T did not delay disease progression, but demonstrated an overall survival benefit compared to placebo. While clinical trials have evaluated the effects of sipuleucel-T on overall survival and progression, more studies are needed to evaluate its effectiveness and role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The treatment consists of ex vivo stimulation of DCs with PA2024 that is a fusion protein of prostatic acid phosphatizes (TAA present in 95% of this type of tumor) and GM-CSF. The Phase III clinical trial revealed increased overall survival of patients treated with Provenge in comparison to placebo ( 86 , 87 ).…”
Section: Dc-based Cancer Immunotherapymentioning
confidence: 99%
“…The treatment consists of ex vivo stimulation of DCs with PA2024 that is a fusion protein of prostatic acid phosphatizes (TAA present in 95% of this type of tumor) and GM-CSF. The Phase III clinical trial revealed increased overall survival of patients treated with Provenge in comparison to placebo ( 86 , 87 ).…”
Section: Dc-based Cancer Immunotherapymentioning
confidence: 99%
“…233,238,256,262,263 As for the main oncological indications investigating in this context, 7 trials enrolled melanoma patients, 226,230,236,238,250,251 4 subjects with pancreatic carcinoma, 220,227,228,248 4 women with breast carcinoma, 222,255,258,260 4 patients with various brain tumors, including glioblastoma; 234,242,249,252 3 ovarian carcinoma patients, 229,235 and the others a broad panel of hematological and solid neoplasms. 221,224,225,[231][232][233]237,[239][240][241]243,244,246,247,253,254,256,257,259,261 Taken together, the results of these studies (the majority of which was Phase I or II trials) indicate that DC-based anticancer interventions are generally well tolerated and elicit anticancer immune responses that, at least in a fraction of patients, underpin objective c...…”
Section: Literature Updatementioning
confidence: 94%
“…260,261 In many instances, DCs were employed as standalone therapeutic agents, i.e., administered in the presence of standard adjuvants only. [221][222][223][224][225]229,232,234,240,243,245,246,[249][250][251] Alternatively, DC-based interventions were administered together with cytokine-induced killer (CIK) cells, 220,233,247,[252][253][254][255] adoptively transferred T lymphocytes, 226,236,239,248,256,259 chemotherapy, 227,228,237 immunostimulatory cytokines, 230,235,242 TLR agonists, 257 or radiation therapy. 233,238,256,262,263 As for the main oncological indications investigating in this context, 7 trials enrolled melanoma patients, 226,230,236,238,250,…”
Section: Literature Updatementioning
confidence: 99%
“…As of 2019, 30 000 men have been prescribed sipuleucel-T. 5 With few exceptions, including 1 institutional retrospective review (36 patients treated with sipuleucel-T) and a clinical trial of androgen-dependent prostate cancer (117 patients treated with sipuleucel-T), 6,7 most of the safety information in the literature [8][9][10][11] is limited to review articles that refer to the clinical trials originally submitted in support of product approval. [12][13][14] We sought to summarize the safety experience of sipuleucel-T in the postmarketing period by assessing US reports submitted to the FDA's Adverse Event Reporting System (FAERS).…”
Section: Introductionmentioning
confidence: 99%